Associations of the Charlson comorbidity index with depression and mortality among the U.S. adults - Ying-Zhao Wang; Chun Xue; Chao Ma; An-Bang Liu; An-Bang Liu (Frontiers Media S.A., 2024)
BackgroundChronic comorbidities are often associated with higher risks of depression and mortality. This study aims to explore the relationships between the Charlson Comorbidity Index (CCI) and depression, and their combined effect on mortality.MethodsThis study made use of data gathered in the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018, including a collective of 23,927 adult participants. According to CCI score distribution, CCI was categorized into three groups (T1 with CCI = 0; T2 with CCI = 1; T3 with CCI ≥ 2). In the CCI ≥ 2 group, patients may have two or more chronic diseases. Multivariable logistic regression models were employed to explore the relationship between CCI and depression. The study utilized the Cox proportional hazards model to investigate the association between CCI, the combination of CCI and depression, and all-cause mortality.ResultsOur analysis revealed that after adjusting for potential confounders, a positive association was found between CCI and depression (OR = 1.25, 95% CI: 1.21, 1.29). Moreover, a greater CCI was found to be closely linked to higher mortality in individuals with depression (HR = 1.14, 95% CI 1.11, 1.18). Stratifying CCI into tertiles, higher tertiles of CCI (T2, T3 vs T1) also showed positive associations with depression and all-cause mortality. For patients with CCI ≥2 (T3) combined with depression, the risk of mortality was significantly elevated compared to those with CCI = 0 (T1) and non-depressed participants (HR = 2.01, 95% CI: 1.60, 2.52).ConclusionThe study findings demonstrate a positive correlation between CCI and the risk of depression, along with an association with increased all-cause mortality among depression patients. Hence, it is important to prioritize the clinical care of patients with a high CCI (≥2) and depression in order to lower the chances of mortality.